IN VITRO ANTIBACTERIAL ACTIVITY OF CHALCONE DERIVATIVES FROM Kaempferia pandurata RHIZOMES AGAINST CLINICAL ISOLATE BACTERIA - Marliyana, Soerya Dewi; Syah, Yana Maolana; Mujahidin, Didin - (ALCHEMY Jurnal Penelitian Kimia, 2017)
In vitro antibacterial activity of chalcone derivatives from “temu kunci” (K. pandurta) rhizomes against clinical isolate bacteria has been done. Two chalcone derivatives, panduratin A (1) and 4-hydroxypanduratin A (2) were isolated from Kaempferia pandurata rhizomes. Isolation of the chemical components were done with extraction (maceration), vacuum liquid chromatography and radial chromatography methods. The structures were determined by NMR spectroscopy (1H-NMR, 13C-NMR, 1D and 2D), then compare with data from literatures. Antibacterial activity was carried out with reference to the CLSI microdilution method, against eight clinical isolate bacteria such as Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysentriae and Vibrio cholerae. Compounds 1 and 2 showed significant antibacterial activity with highest activity against S. aureus and B. subtilis with MIC values of 2.4 to 18.8 µg/mL and MBC values of 4.8 to 37.5 µg/mL. These results showed these compounds as potential antibacterial agent for clinical isolate bacteria.